Plasticity-promoting effect of melatonin after experimental cerebral ischemia - Kılıç, Ülkan; Elibol, Birsen; Beker, Mustafa Çağlar; Çağlayan, Ahmet Burak; Altuğ Tasa, Burcugül; Beker, Merve; Özen, Mustafa; Yılmaz, Bayram; Kılıç, Ertuğrul (Wiley-Blackwell, 2016)
[Abstract Not Available]
Keywords: Plasticity; Experimental; Cerebral Ischemia